Acetylation of lysine 7 of AhyI affects the biological function in Aeromonas hydrophila. (March 2020) - Li, Dong; Ramanathan, Srinivasan; Wang, Guibin; Wu, Yao; Tang, Qi; Li, Guohui
Abstract: Acyl-homoserine-lactone synthase (AhyI) of Aeromonas hydrophila can produce quorum sensing (QS) auto-inducer 1 (AI-1) type signal molecule, which plays important roles in various biological phenomenons such as biofilm formation, hemolysin production and motility. Previous research revealed that the AhyI of A. hydrophila has acetylation modification on lysine 7 site, but its intrinsic biological function is still largely unknown. To study the effect of AhyI protein and its acetylation modification on the physiological traits of A. hydrophila, the site-directed mutagenesis strains including ΔahyI::ahyI-K7Q and ΔahyI::ahyI-K7R were made in this study. The mutation at K7 site of lysine acetylation in AhyI protein decreased the protease production, but the lysine acetylations do not affect the biofilm formation and hemolysin production. To further study the effect of lysine acetylation on AI-1 signal molecule production, the acyl-homoserine lactones (AHLs) extraction and bioluminescence quantification were performed. Compared with the rescue strain, the acetylation on K7 of AhyI resulted in a decreased level of AHLs and bioluminescence production. It indicated that the lysine acetylation modification on the AhyI protein can regulate the production of signalling molecules. Overall, the obtained data in this study provide a theoretical basis for further understanding the role of lysine acetylation of AhyI protein and lay a foundation to systematically study the regulatory mechanism of QS. Highlights: The AhyI protein regulates various quorum sensing regulated virulence factors productions in Aeromonas hydrophila. The AhyI protein showed lysine acetylation at their K7 site. The lysine acetylation at K7 site of AhyI protein affects various biological functions in Aeromonas hydrophila.